2008
DOI: 10.1253/circj.72.449
|View full text |Cite
|
Sign up to set email alerts
|

Management of Left Subclavian Artery in Endovascular Stent-Grafting for Distal Aortic Arch Disease

Abstract: linically, intentional occlusion of the left subclavian artery (LSA) has been done to exclude a distal aortic arch aneurysm during endovascular stentgrafting. [1][2][3][4][5] However, the LSA is crucial for patients with critically stenosed carotid or vertebral arteries or a functionally compromised circle of Willis, and also for those who have undergone coronary artery bypass grafting using the left internal thoracic artery (LITA). We have attempted to save the LSA by using hand-made fenestrated stent grafts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…6 TEVAR outcomes including occurrence and characteristics of endoleaks depend on the anatomic factors of the aortic disease. 7,8 Several reports describing heterogeneous pathologic processes have indicated that endoleaks are associated with anatomic factors, such as the diameter of the aneurysm, radius of the aortic curve, coverage of the left subclavian artery (LSCA), and tortuosity of the aorta, and procedural factors, such as the diameter, length, number, and completeness of apposition of the stent grafts. [9][10][11] Tortuosity of the aorta is reportedly related to the formation of endoleaks and bird-beak configuration; however, thus far, the methods used to calculate tortuosity have not been consistent with the reporting standards for TEVAR described by the Society for Vascular Surgery, 12,13 which aim to standardize findings regarding TEVAR.…”
mentioning
confidence: 99%
“…6 TEVAR outcomes including occurrence and characteristics of endoleaks depend on the anatomic factors of the aortic disease. 7,8 Several reports describing heterogeneous pathologic processes have indicated that endoleaks are associated with anatomic factors, such as the diameter of the aneurysm, radius of the aortic curve, coverage of the left subclavian artery (LSCA), and tortuosity of the aorta, and procedural factors, such as the diameter, length, number, and completeness of apposition of the stent grafts. [9][10][11] Tortuosity of the aorta is reportedly related to the formation of endoleaks and bird-beak configuration; however, thus far, the methods used to calculate tortuosity have not been consistent with the reporting standards for TEVAR described by the Society for Vascular Surgery, 12,13 which aim to standardize findings regarding TEVAR.…”
mentioning
confidence: 99%
“…landing zone should be non-dissected aorta, generally, which is the aortic arch in cases of acute type B aortic dissection. Based on our study, there is a risk of complication around 5 % if LSA is simply covered by a stent graft (Kurimoto Y, et al, 2008a(Kurimoto Y, et al, , 2009). In addition of cerebral complication, a simple coverage of LSA possibly increases a risk of spinal cord ischemia as postoperative complication.…”
Section: Ruptured Acute Type B Aortic Dissectionmentioning
confidence: 72%
“…Recently a new strategy to manage LSA has been reported with the development of a branched stent-graft designed to maintain the normal antegrade flow into the LSA [10-12, 24,25].…”
Section: Discussionmentioning
confidence: 99%